FAKTOR YANG MEMPENGARUHI KEJANG DEMAM PADA ANAK DI RUANG RAWAT INAP RSUD PRAMBANAN - S Supardi; Fitri Suciana; Ambar Winarti; Neti Amayawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Fever seizures in children caused by an increase in body temperature of more than 380C. In Indonesia, febrile seizures occur in 2-4% of children aged 6 months-5 years. Fever seizures in children can be influenced by various factors including age, gender, high temperature, family history of seizures, infectious diseases. This study aims to determine the relationship between the level of family anxiety during the Covid 19 pandemic regarding treatment and the incidence of withdrawal from schizophrenic patients at Dr. RM. Soedjarwadi, Central Java Province. This type of research is an observational analytic, case control study design with a retrospective approach. The sampling technique used total sampling. The number of children with febrile seizures was 44 respondents and 44 respondents did not have fever seizures so that the total sample was 88 respondents. Retrieval of data using medical records. Univariate statistical test using frequency distribution, bivariate using chi square test and multivariate using multiple logistic regression test. The results obtained in the case group, most of the respondents were 12-36 months (61.4%), male (65.9%), had a body temperature> 380C (59.1%), no history of febrile seizures. in the family (72.7%) and there is an infectious disease (97.7%), while the control group is mostly respondents aged 12-36 months (65.9%), male (54.5%), body ≤380C (65.9%), there was no family history of febrile seizures (90.9%) and there was an infectious disease (86.4%). Factors associated with the incidence of febrile seizures were body temperature (p value 0.019), family history of seizures (p value 0.027) and childhood infectious disease (p value 0.049) while age (p value 0.448) and gender (p value 0.276) were not. associated with the incidence of febrile seizures. The conclusion of this study is that the most influencing factor on febrile seizures is a family history of seizures with a p value of 0.034 (p <0.05), children who have a history of family febrile seizures are at risk of 3.902 times experiencing febrile seizures.